Mucocutaneous manifestations in patients with chronic kidney disease: A cross-sectional study - Rattan S Rashpa; Vikram K Mahajan; Pankaj Kumar; Karaninder S Mehta; Pushpinder S Chauhan; Ritu Rawat; Vikas Sharma (Wolters Kluwer Medknow Publications, 2018)
Background: Chronic kidney disease (CKD)-associated mucocutaneous manifestations significantly impair the quality of life but often remain understudied. They may also vary across regions, socioeconomic and nutritional status, and racial differences. Objectives: To study the patterns of mucocutaneous disorders and their prevalence in CKD patients irrespective of clinical stage or dialysis status. Materials and Methods: 122 (M:F = 77:45) patients aged 21‒85 (Mean ± SD = 57.5 ± 14.0) years having CKD for 3 month to 5 years were studied for mucocutaneous manifestations. Fifty (41%) patients were on hemodialysis for 1‒42 months. Detailed medical history, clinical and mucocutaneous examination, and lab investigations were performed. KOH mounts, skin biopsy, Gram's and Giemsa staining, bacterial or fungal cultures were performed as required. Results: Xerosis in 93 (76.2%), skin pallor in 61 (50%), pruritus in 57 (46.7%), pigmentation in 47 (38.5%), and purpura in 18 (14.8%) patients were the major dermatoses. Bullous lesions and perforating folliculitis occurred in 3 (2.5%) patients each. Major nail abnormalities were pallor (in 35.2%), absent lunula (in 23.8%), nail discoloration (in 18%), and "half-and-half nails" in 16.4% patients, respectively. Hair abnormalities included sparse scalp and body hairs (in 35.2% and 13.1%, respectively) and lusterless hair in 12.3% patients. Coated tongue (in 14.8%), xerostomia (in 12.3%), and macroglossia with teeth indention (in 7.4%) patients were the mucosal manifestations. Conclusions: Xerosis, pruritus, skin pallor/pigmentary changes, nail pallor, absent lunula, nail discoloration, sparse hairs, coated tongue, xerostomia, macroglossia, and infections were the most common mucocutaneous manifestations in the studied patients irrespective of hemodialysis status. Cold and dry climates might be additional aggravators for xerosis/pruritus. Lifelong follow-up may be needed to reduce the morbidity associated with CKD/hemodialysis specific dermatoses appearing over a period.